Naskah-Naskah Tradisi Lisan Riau Upaya Penyelamatan Aset Budaya Melayu - Mahyudin Syukri (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
This article represent to answer the problems which emerge authenticity of oral tradition as cultural element or source and values application which consist in it, or at last saving to cultural asests which stem from oral tradition, specially oral traditioan that growing and expanding in society of Riau. Some of oral tradition of Riau society in this time have succeded to present in the form of article, representing a saving to local cultures which is’t not written will lose to be swallowed by time, but that way non meaning nothing like other oral tradition which is life and expand by it saving effort, so that this, tradition remain to be looked after, and is not totally disappeared swallowed by time, because each every submitted sent the message always containt of norms and values which of course of teaching of religi which they embrace, (Islam)